IMPROVING FAMILY SUPPORT ON PREVENTING OBESITY CHILDREN THROUGH FOCUS GROUP DISCUSSION - Firnaliza Rizona; Yeni Anna Appulembang; Fuji Rahmawatif (Proceeding B-ICON, 2022)
The number of childhood obesity has increased strikingly in the world over the past 3 decades. The family support was needed specially to prevent and resolve obesity on school age children. This study aimed to know the effect of focus group discussion for increasing family support to prevent and resolve the obesity problem on children. This study was used pre-experimental method to analyze the data. The number of family was 20 mothers at elementary school in Palembang city —the data was collected by using questioner after conducting focus group discussion. The statistic result showed that was an increasing family support number with p-value =0,034. Focus group discussion could become a method for increasing family support to children. Family could give information about obesity, provide a good nutrition, and optimized physical activity to children.